Pengaruh Disiplin Kerja, Motivasi, dan Kompensasi terhadap Kinerja Karyawan - Laksmi, Ida Ayu Putu Anggita; Suasti Puja, I Made (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This research aims to determine the effect of disiplin kerja, non-performance. The aim of this research is to determine the effect of work discipline, motivation and compensation on employee performance at the Agung Mandiri Cooperative in Sukawati, Gianyar. The population in the study was all 32 employees of the Agung Mandiri Cooperative in Sukawati Gianyar. The sampling method used a saturated sample because the population was relatively small. Data was collected using a questionnaire and analyzed using multiple linear regression analysis. Based on testing, it shows that work discipline has a positive and significant effect on employee performance at the Agung Mandiri Cooperative in Sukawati, Gianyar. Work motivation has a positive and significant effect on employee performance at the Agung Mandiri Cooperative in Sukawati Gianyar. Compensation has a positive and significant effect on employee performance at the Agung Mandiri Cooperative in Sukawati Gianyar. It is recommended that the Agung Mandiri Cooperative in Sukawati Gianyar provide strict sanctions to employees who are still unable to comply with company regulations, provide training to employees, and provide good incentives to increase employee morale so that employees are able to show even better performance.